Diagnostic tools validated by ICARDA’s Germplasm Health Unit (GHU) for detection of legume seed-borne pests - Kumari, Safaa; Moukahel, Abdulrahman; El Miziani, Inaam (International Center for Agricultural Research in the Dry Areas, 2022)
ICARDA’s Germplasm Health unit (GHU) is responsible for the monitoring, clearance and documentation of safe germplasm movement at the Center's locations in Lebanon and Morocco. All incoming and outgoing genetic resources and breeding germplasm must go through a strict quarantine monitoring system, including seed health testing. To confirm the health status of seed samples, the GHU conducts different types of tests based on the nature of the pest to be identified. In this manual, we listed and described the procedures of diagnostic tools validated by ICARDA’s GHU for detection of legume seed-borne pests: